The influence of non-breathing-related sleep fragmentation on cognitive function in patients with cerebral small vessel disease - Wang J (Dove Medical Press, 2019)
Jihui Wang,1,* Xiaodong Chen,2,* Jinchi Liao,2 Li Zhou,3 Siyuan Liao,2 Yilong Shan,2 Zhengqi Lu,2 Jiong Tao1 1Department of Psychiatry, The Third Affiliated Hospital, Sun Yat-sen University, Guangzhou, 510630, People’s Republic of China; 2Department of Neurology, The Third Affiliated Hospital, Sun Yat-sen University, Guangzhou, 510630, People’s Republic of China; 3Department of Rehabilitative Medicine, The First Affiliated Hospital of Clinical Medicine of Guangdong Pharmaceutical University, Guangzhou, 510080, People’s Republic of China *These authors contributed equally to this work Background: Cognitive impairment in patients with cerebral small vessel disease (CSVD) is common, but the pathogenic mechanism is not well understood. The situation of non-breathing-related sleep fragmentation in CSVD patients and its influence on cognitive impairment is not clear. The aim of this study was to investigate the influence of non-breathing-related sleep fragmentation on cognitive function in patients with CSVD.Methods: A group of 89 CSVD patients without breathing-related sleep disorders in the Department of Neurology, Third Affiliated Hospital of Sun Yat-sen University was enrolled. The patients underwent magnetic resonance scan, polysomnography, cognitive function evaluation using Montreal Cognitive Assessment scale (MoCA), and Mini-Mental State Examination. The patients were assigned to study group (arousal index [ArI] ≥26.8/hour) or control group (ArI <26.8/hour) based on the average level of ArI (mean =26.8, SD =7.5) at night, and the cognitive function of the patients in the two groups was analyzed.Results: The total MoCA score, the subscale scores of visuospatial ability and delayed recall in the study group were significantly lower than that in the control group (P<0.05). The cognitive impairment measured by MoCA was positively related to ArI level and %N-3 sleep according to the results of logistic regression (P<0.05).Conclusion: Non-breathing-related sleep fragmentation is associated with cognitive impairment in CSVD patients, especially executive function and delayed recall ability. Keywords: cerebrovascular disorders, sleep, fragmentation, cognition, polysomnography